2014
DOI: 10.1016/j.echo.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Memory Imaging in Nonhuman Primates with Echocardiographic Molecular Imaging of Selectin Expression

Abstract: Background Selectins are adhesion molecules that are expressed by the vascular endothelium upon activation and may be an imaging target for detecting myocardial ischemia long after resolution. We hypothesized that molecular imaging of selectins with myocardial contrast echocardiography (MCE) molecular imaging could be used to detect recent brief ischemia in closed-chest non-human primates. Methods Myocardial ischemia was produced in anesthetized adult rhesus macaques (n=6) by percutaneous balloon catheter oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…It has been shown that in the post-ischemic myocardium, ultrasound molecular imaging signal substantially increased 3–10 fold using microbubbles targeted to P-selectin in mice [26] and rats [25] after transient myocardial ischemia. Using a non-human primate transient myocardial ischemia model, dual P- and E-selectin-targeted ultrasound of ischemic memory using the same contrast agent described above for IBD imaging has been recently translated from small to large animals with a 240±85% increase in the molecular imaging signal in ischemic myocardium compared to non-ischemic myocardium [27]. Since E-selectin expression is under transcriptional control and cell surface expression can be detected approximately two hours after acute stimulation [27], dual-targeting to both P- and E-selectin is advantageous as imaging signal can be detected from a few minutes up to several hours after the ischemic event.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the post-ischemic myocardium, ultrasound molecular imaging signal substantially increased 3–10 fold using microbubbles targeted to P-selectin in mice [26] and rats [25] after transient myocardial ischemia. Using a non-human primate transient myocardial ischemia model, dual P- and E-selectin-targeted ultrasound of ischemic memory using the same contrast agent described above for IBD imaging has been recently translated from small to large animals with a 240±85% increase in the molecular imaging signal in ischemic myocardium compared to non-ischemic myocardium [27]. Since E-selectin expression is under transcriptional control and cell surface expression can be detected approximately two hours after acute stimulation [27], dual-targeting to both P- and E-selectin is advantageous as imaging signal can be detected from a few minutes up to several hours after the ischemic event.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study on non-human primates with myocardial ischaemia, UMI was shown to be both safe and effective for imaging recent myocardial ischaemia. Lipid-coated MBs functionalised with dimeric recombinant human P-selectin glycoprotein ligand-1, a recombinant ligand appropriate for humans, were used [175]. The study suggests that UMI can be useful for detecting recent ischaemia in patients with chest pain, even in the absence of necrosis [175].…”
Section: In Vivo Molecular Imagingmentioning
confidence: 99%
“…Molecular imaging of resolved ischemia without infarction has been performed with myocardial contrast echocardiography (MCE) in rodent and nonhuman primate models using microbubbles targeted to the selectin family of endothelial cell adhesion molecules that are rapidly expressed in response to ischemia (4)(5)(6)(7). Clinical translation of this approach has been slowed by the arduous regulatory process of testing efficacy and safety of a human-ready microbubble agent bearing a biologically active ligand.…”
mentioning
confidence: 99%